2011
DOI: 10.1017/cbo9781139105378
|View full text |Cite
|
Sign up to set email alerts
|

Leçons sur les maladies du système nerveux

Abstract: Jean-Martin Charcot (1825–93) was a professor of anatomical pathology at the Pitié-Salpêtrière Hospital in Paris, and one of the founders of modern neurology. Numerous disorders are named after him, and he was one of the best known doctors in nineteenth-century France. He was the first to describe and name multiple sclerosis, and undertook crucial research into what became known as Parkinson's Disease. He also worked on hysteria, and was one of Freud's teachers. These two volumes of lectures on neurological il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 0 publications
0
25
0
2
Order By: Relevance
“…Elle est basée sur l'observation de 40 patientes, et comporte une description précise des déformations des mains qui sera affinée, un peu plus de 10 ans plus tard dans un livre célèbre et qui sera même traduit en anglais : Leçons cliniques sur les maladies des vieillards et les maladies chroniques [7]. La thèse de 1853 comporte 6 autopsies, dans lesquelles sont décrits, au niveau des articulations disséquées, le pannus synovial, les ulcérations cartilagineuses et la raréfaction osseuse.…”
Section: La Carrière De Charcotunclassified
“…Elle est basée sur l'observation de 40 patientes, et comporte une description précise des déformations des mains qui sera affinée, un peu plus de 10 ans plus tard dans un livre célèbre et qui sera même traduit en anglais : Leçons cliniques sur les maladies des vieillards et les maladies chroniques [7]. La thèse de 1853 comporte 6 autopsies, dans lesquelles sont décrits, au niveau des articulations disséquées, le pannus synovial, les ulcérations cartilagineuses et la raréfaction osseuse.…”
Section: La Carrière De Charcotunclassified
“…Several clinical courses are usually distinguished in multiple sclerosis (Jekyll Island Meeting of MS Society 1995, reported in Lublin, 1996 ), but it remains uncertain whether they reflect different neuropathological mechanisms. It is well established that axonal injury is a feature of multiple sclerosis (Charcot, 1880 ), that the extent of axonal injury is correlated with the degree of inflammation (Trapp et al , 1998 ) at least in relapsing multiple sclerosis, and that a close association between inflammation and neurodegeneration might exist in all disease stages of multiple sclerosis (Kutzelnigg et al , 2005 ; Frischer et al , 2009 ). However, the interdependence between focal inflammation, diffuse inflammation and neurodegeneration, and their relative contribution to clinical deficits remain ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the classic concept of hypnoid states applied in the studies of trauma-related hysteria developed by Charcot (1887) and others has found renewed attention: peritraumatic dissociation (PD) during or immediately following a traumatic event is considered to be an important risk factor for the development of mental health disturbances such as PTSD. Examples of dissociative reactions in this phase include a sense of emotional numbing or detachment, reduced awareness of one's surroundings, and/or distortions in the perception of reality, body and time (Bryant, 2007; Kolk & Van der Hart, 1989).…”
Section: Introductionmentioning
confidence: 99%